Safety of Ovaleap® (Follitropin Alfa) in Infertile Women Undergoing Superovulation for Assisted Reproductive Technologies: A Multinational Comparative, Prospective Cohort Study - Kaplan, Sigal; Levy-Toledano, Rachel; Davies, Miranda; Roy, Debabrata; Howles, Colin M.; Lass, Amir (Frontiers in Endocrinology, 2021)
Background: Ovaleap® (follitropin alfa), a recombinant human follicle stimulating hormone, is a biosimilar medicinal product to Gonal-f® and is used for ovarian stimulation. The main objective of this study was to assess the safety and effectiveness of Ovaleap® compared to Gonal-f® in one treatment cycle in routine clinical practice. Methods: SOFIA was a prospective cohort study conducted in six European countries. Eligible patients were infertile women undergoing superovulation for assisted reproductive technology, who were administered Ovaleap® or Gonal-f® for ovarian stimulation and were naïve to follicle stimulating hormone treatment. The recruitment ratio was 1:1. The primary endpoint was incidence proportion of ovarian hyperstimulation syndrome (OHSS) and the secondary endpoint was OHSS severity (Grades I, II, III). The effect of risk factors or potential confounders on the odds ratio for OHSS incidence as well as treatment effect on OHSS incidence was explored using univariate logistic regression. Pregnancy and live birth rates were also assessed. Results: A total of 408 women who were administered Ovaleap® and 409 women who were administered Gonal-f® were eligible for analysis. The incidence proportion of OHSS was 5.1% (95% CI: 3.4, 7.7) in the Ovaleap® cohort and 3.2% (95% CI: 1.9, 5.4) in the Gonal-f® cohort. This difference in OHSS incidence proportion between the two cohorts was not statistically significant neither before (p=0.159) nor after univariate adjustment for each potential confounder (p>0.05). The incidence proportion of OHSS severity grades was similar in the two treatment groups (3.4% versus 2.0% for Grade I, 1.2% versus 1.0% for Grade II, and 0.5% versus 0.2% for Grade III, in the Ovaleap® and Gonal-f® cohorts, respectively), without a significant statistical difference (p=0.865, for each grade). Among patients who had embryo transfer, clinical pregnancy rates were 33% and 31% and live birth rates were 27% and 26%, in the two cohorts, respectively. Conclusions: Findings from the SOFIA study indicate that the incidence proportions of OHSS and OHSS severity, as well as pregnancy and live birth rates, are similar between Ovaleap® and Gonal-f® treatments and corroborate the safety and effectiveness of Ovaleap® as a biosimilar to Gonal-f®.